Peculiarities of labor of medical and pharmaceutical workers: a comparative analysis of legislations of Kazakhstan and some OECD countries - Galiakbarova, Guzal (Problems of legality, 2021)
This article discusses some issues of labor regulation of medical and pharmaceutical workers, the peculiarities of health systems in some countries of the Organization for Economic Cooperation and Development, a comparative analysis of their experience and Kazakhstan is carried out. The specificity of the legal status of medical and pharmaceutical workers is also considered, which is explained by the fact that its regulation is based not only on general norms of labor law, but also on special regulations affecting various features of the activities of this category of workers. At the same time, it is noted that the basis of the legislative regulation of the work of medical and pharmaceutical workers is the generally recognized principles and norms of international law, as well as the norms of national legislation. The article focuses on the fact that among the variety of sources concerning the legal status of various categories of workers, there is no separate comprehensive study devoted to the peculiarities of legal regulation of both medical and pharmaceutical workers, in connection with which the chosen topic of scientific research is updated.